Infective endocarditis with perivalvular abscess following sutureless valve implantation, successfully treated with aortic root reconstruction and biological Bentall procedure - Ryo Fujimoto; Shingo Hirao; Tatsuhiko Komiya (Journal of Cardiothoracic Surgery)
Abstract Background Aortic valve prosthetic infections can lead to the spread of infection, causing annular abscesses and annular destruction, which may require annular reconstruction and aortic root replacement. Reports on the infection and reoperation of sutureless valves are rare. Here, we present a case of infection involving a Perceval sutureless valve, which led to an annular abscess. Case presentation We report the case of a 73-year-old woman who had previously undergone sutureless valve implantation for severe stenosis of a bicuspid aortic valve. Approximately 23 months after surgery, the patient developed recurrent Methicillin-resistant Staphylococcus aureus bacteremia and was admitted to the hospital. Following a thorough assessment, she was diagnosed with a prosthetic valve infection and an annular abscess, necessitating surgical intervention. Intraoperatively, significant annular destruction was evident after the valve was removed. The aortic root was reconstructed with a bovine patch and Bentall surgery was accomplished using a composite graft consisting of a biological valve and a Valsalva graft. The patient was discharged in good general condition with no significant post-operative complications. Conclusions One of the issues with using a Perceval valve is that in the event of infection, it can lead to the spread of infection from the aortic root to the left ventricular outflow tract, potentially requiring extensive debridement and aortic root replacement.